EVALUATION OF ANTIMICROBIAL ACTIVITY OF SEED EXTRACT FROM PLANT INGUDI (BALANITES AEGYPTIACA LINN. DELILE) - Sanjeev, Kumar; Deepika, Singh; Kumar, Abhishek; Kamal Nayan, Dwivedi (International Journal of Ayurveda and Pharma Research, 2015)
Evaluation of antimicrobial activity of hydro-alcoholic extract of Ingudi (Balanites Aegyptiaca Linn. Delile.) was done against human pathogens. The antimicrobial activity of newly synthesized compound was first screened by disc diffusion method against Gram positive Enterococcus faecalis, Staphylococcus aureus ATCC 25323 and Gram negative Pseudomonas aeruginosa ATCC 27893, Escherichia coli ATCC 25922, human pathogenic bacteria and fungal strains of candida (C. albicans, C. tropicalis) according to the guidelines of National Committee for Clinical Laboratory Standards (NCCLS, 1997). Fresh grown bacteria were mixed in sterile saline (0.85%) and the turbidity was matched with McFarland No. 2 system to achieve concentration of 107 CFU/ml. Sterile petri plates containing 20 mL of Mueller Hinton agar (MHA, Hi-Media) were used for all bacterial culture. The bacterial innoculum suspension were spread on the surface of agar plates and allowed to solidify for 5 min. Sterile disc (5mm) of Whatman paper no. 1 was then placed on the surface of the media and the test compounds (25µl/ml) was put and allowed to diffuse and plates were incubated for 24 h at 37°C for bacterial cultures and fungal culture were incubated for 72 hr at 25°C. DMSO was used as negative control, Ciprofloxacin (5µg/disc, Hi-Media) was used as positive control for bacteria. The highest antibacterial potential was exhibited by Gram positive bacteria Staphylococcus aureus ATCC 25323 and Gram negative Pseudomonas aeruginosa ATCC 27893 among tested microorganisms.